STUDY OF ESTRUS SYNCHRONIZATION IN CROSSBRED CATTLE AND BUFFALOES IN JAIPUR AND BHARATPUR DISTRICTS OF RAJASTHAN-PT-II (Indian Journal of Animal Production and Management, 2014)
Present study evaluated pregnancy rate and estrus responses to treatment using the estrus synchronization protocol in crossbred cattle and buffaloes. Since, the study was carried out at field level, animals selected at random belonged to both the species, irrespective of parity, milk yield and body weight. The estrous synchronization protocol was evaluated using treatment with Receptal -2.5ml I/M and fixed time insemination (FTAI) was done 16-24 h post Receptal -2.5ml I/M injection. According to the protocol, the percentage of pregnant animals was observed to be 50.81%. The percentage of pregnant animals to first service resulting on application of protocol for crossbred and buffaloes were recorded 48.0% (12/25) and 52.77% (19/36), respectively.
Keywords: Synchronization; Buffalo; Crossbred; Artificial Insemination; Estrus